DESIGN AND BUILD A SECURITY PARKING SYSTEM BASED ON ARDUINO PRO MICRO AND INTERNET OF THINGS - Susanto; Priyono Yulianto; Dody Wahjudi; Isra’ Nuur Darmawan (Program Studi Teknik Elektro Universitas Peradaban, 2023)
This research is motivated by the problem that since the outbreak of the corona virus in Indonesia, many efforts have been made by the government to prevent the corona virus starting from special regulations with health protocols and the creation of new prevention tools. Problems are not only with the corona virus but security in motorbike and car parking lots which can cause many problems, ranging from theft and misunderstanding. From these problems the researchers created a security system for preventing corona viruses and crime in parking lots, the system created combines the Arduino pro micro and nodemcu microcontrollers as IOT devices that function to send RFID and ESP32Cam readings to a webserver in the form of data, the MLX90614 sensor as a human temperature reading . After testing the temperature sensor used in this study has an accuracy similar to that of a thermogun and digital thermometer with a difference of 0.044ºC and 0.136ºC, the webserver can display the result data from RFID and ESP32Cam readings, comparison of the sensor responses at the entrance has an average result the average response with a difference in time is 0.93 seconds, while at the exit the average difference in time is 1.154 seconds and both of them can open the door latch